2016
DOI: 10.1007/s00380-016-0877-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum angiotensin-converting enzyme 2 concentration and angiotensin-(1–7) concentration in patients with acute heart failure patients requiring emergency hospitalization

Abstract: The existence of a new cascade, angiotensin-converting enzyme (ACE) 2/angiotensin (Ang)-(1-7)/Mas receptor axis, has been recently established in the renin-angiotensin system. However, the dynamics of this cascade under various pathological conditions in clinical settings is still unclear. Forty-nine patients who underwent emergency hospitalization because of acute heart failure (AHF) consented to participate in this study. Thirty-eight healthy volunteers served as controls. Serum ACE activity, ACE2, Ang-(1-7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…In humans, plasma ANG II concentrations in healthy volunteers were reported to be 5~35 fmol/ml (249). Recent human studies reported that ANG II and ANG (1-7) concentrations in healthy volunteers were~8.7 fmol/ml and 3.4 -5.6 fmol/ml, respectively (385,761). Physiological plasma and kidney concentrations of ANG II were reported to be~50 fmol/ml and~160 fmol/g in rats, which increased to~130 fmol/ml and~350 fmol/g, respectively, upon 2 wk ANG II infusion (40 ng/min per 180 -200 g) (1280).…”
Section: Limitations and Pitfalls In Ang II Signaling Researchmentioning
confidence: 99%
“…In humans, plasma ANG II concentrations in healthy volunteers were reported to be 5~35 fmol/ml (249). Recent human studies reported that ANG II and ANG (1-7) concentrations in healthy volunteers were~8.7 fmol/ml and 3.4 -5.6 fmol/ml, respectively (385,761). Physiological plasma and kidney concentrations of ANG II were reported to be~50 fmol/ml and~160 fmol/g in rats, which increased to~130 fmol/ml and~350 fmol/g, respectively, upon 2 wk ANG II infusion (40 ng/min per 180 -200 g) (1280).…”
Section: Limitations and Pitfalls In Ang II Signaling Researchmentioning
confidence: 99%
“… 30 Several other studies have shown that Ang-(1–7) concentrations are often very low or immeasurable in states of health and disease. 31 , 32 While we did not measure ACE2 activity, we are the first to quantify the effector molecules of the alternative RAS in these patients. Our results suggest that Ang-(1–7) might be quickly metabolized to Ang-(1–5) in patients without ACE inhibitors as most patients without RAS blockade or on ARB had detectable Ang-(1–5) levels, indicating an ongoing activity of the alternative RAS axis.…”
Section: Discussionmentioning
confidence: 99%
“…Hisatake et al [16] reported that patients with acute heart failure had lower serum ACE activity and plasma aldosterone concentrations than healthy volunteers, whereas there were no differences between the two groups in terms of plasma renin activity or plasma Ang II concentrations. Patients with acute heart failure had higher serum ACE2 concentrations than healthy volunteers (+64%; P = 0.002), but their serum Ang-(1–7) concentrations were significantly lower (–23%; P = 0.005).…”
Section: Expression and Enzyme Functions Of Ace2mentioning
confidence: 99%
“…An European review [16] has shown that there is no clear evidence that hypertension per se is a risk factor for infection with SARS-CoV-2 or for severity of COVID-19. The study even appears to suggest that ACE inhibitors and ARBs could be associated with a relative protective effect against SARS-CoV-2 infection and, in affected patients, with a better prognosis.…”
Section: How Do Ras Blockers Affect Covid-19?mentioning
confidence: 99%